Prospects Of Development Of Sorghum As Ruminant Feed-In Indonesia - Inge Korima; Mansyur Mansyur; Hendi Setiyatwan (Unpad Press, 2022)
Sorghum plants can be developed in Indonesia as feed for ruminants. This is due to agro-ecological conditions that can be tolerant of land conditions in Indonesia. Dry land can be used for the growth of sorghum because sorghum is a cereal with low water content. The harvest method can be carried out at the age of 85 days to 90 days, due to the high content of organic matter, dry matter, and crude protein. By-products of sorghum or sorghum waste in the form of leaves and stems can be used as forage for ruminants. Antinutrient substances in sorghum can be processed with silage technology to maintain nutrients, feed reserves for a long time, and increase digestibility in the rumen of ruminants to increase feed efficiency.